2020
DOI: 10.1007/s00018-020-03508-9
|View full text |Cite
|
Sign up to set email alerts
|

HOX gene cluster (de)regulation in brain: from neurodevelopment to malignant glial tumours

Abstract: HOX genes encode a family of evolutionarily conserved homeodomain transcription factors that are crucial both during development and adult life. In humans, 39 HOX genes are arranged in four clusters (HOXA, B, C, and D) in chromosomes 7, 17, 12 and 2, respectively. During embryonic development, particular epigenetic states accompany their expression along the anterior-posterior body axis. This tightly regulated temporal-spatial expression pattern reflects their relative chromosomal localization, and is critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 205 publications
4
41
0
Order By: Relevance
“…DNA methylation pattern alterations, a hallmark of cancer cells, could contribute to the observed HOX gene deregulation. However, while this mark represses promoter activity, HOX genes are documented to be hypermethylated in glioma samples [18]. Specifically, we previously observed that a class of genes characterized by an aberrant gain of both expression and DNA methylation at their CpG island (CGI) promoter in IDH wt glioma samples is precisely highly enriched for HOX genes [22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA methylation pattern alterations, a hallmark of cancer cells, could contribute to the observed HOX gene deregulation. However, while this mark represses promoter activity, HOX genes are documented to be hypermethylated in glioma samples [18]. Specifically, we previously observed that a class of genes characterized by an aberrant gain of both expression and DNA methylation at their CpG island (CGI) promoter in IDH wt glioma samples is precisely highly enriched for HOX genes [22].…”
Section: Resultsmentioning
confidence: 99%
“…In line with the absence of HOX gene expression in healthy brain, most HOX genes were upregulated, and only HOXD1 and HOXD‐AS1 , which are expressed in healthy brain, were downregulated in IDH wt samples. This observation suggests that deregulation affects all four HOX clusters and does not follow the coordinated collinear expression observed during normal embryonic development [18]. Given the key role of HOX transcription factors during normal development, it is reasonable to hypothesize that HOX gene upregulation contributes to gliomagenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other family members in the HOX family are also involved in tumor progression, including leukemia, breast cancer, lung cancer and so on (45,46). For instance, abnormal expressions of HOXA6, HOXA7, HOXA9, HOXA13, HOXB13, HOXD4, HOXD9, HOXD10, and HOXD13 were noticed in tumor tissue by comparing with normal tissue (47).…”
Section: Discussionmentioning
confidence: 99%
“…Homeobox genes encode transcription factors that regulate the expression of several genes during embryogenesis [1]. Among them, Hox genes are very well described as specifying the anteroposterior pattern as well as the development of many organs [2], for example during neurodevelopment as well as in malignant glial tumors and as gliomas and glioblastomas [3]. Within this gene cluster, introns represent a hypothetically rich source of microRNAs (miRNAs).…”
Section: Introductionmentioning
confidence: 99%